1989
DOI: 10.1007/bf01963901
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the BCB Roche and Oxoid Signal blood culture systems

Abstract: The agar-slide blood culture system BCB Roche was compared with the Oxoid Signal blood culture system using 2,266 paired blood cultures. A total of 271 (12%) paired sets were culture-positive, including 222 (9.8%) yielding pathogens associated with septicemia and 50 (2.2%) yielding likely contaminants. In the recovery of the total 235 isolates considered as pathogens, the BCB Roche system yielded 202 (85.9%), the Oxoid Signal 211 (89.8%); 178 (75.7%) were cultured by both systems. There was no statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…about 10 mL per adult patient [17, 57]. At the University Hospital Geneva, we found that the Signal system detected facultatively and strictly anaerobic bacteria well, which was complementary to the Septi‐Chek aerobic system [8, 9, 42, 43]. Similar findings were also reported elsewhere [39].…”
Section: Manual Systemssupporting
confidence: 88%
See 1 more Smart Citation
“…about 10 mL per adult patient [17, 57]. At the University Hospital Geneva, we found that the Signal system detected facultatively and strictly anaerobic bacteria well, which was complementary to the Septi‐Chek aerobic system [8, 9, 42, 43]. Similar findings were also reported elsewhere [39].…”
Section: Manual Systemssupporting
confidence: 88%
“… Yield of pathogens and contamination rate of 10 498 manual aerobic blood‐culture vials (Septi‐Chek BHI, Signal and Hémoline) related to the volume of blood cultured. On average, 9±2.8 mL of blood was inoculated during the studies performed at the University Hospital Geneva [8, 9]. …”
Section: General Considerations On Blood‐culture System Evaluationsmentioning
confidence: 99%
“…Results of evaluation of the commercially available blood culture systems BCB Roche (Hoffmann-La Roche, Switzerland) and Oxoid Signal (Oxoid, UK) have been favourable, the two systems constituting a valuable blood culture set for detection of aerobic and anaerobic microorganisms (1,2). With the intention of improving the detection rate of the BHI-S broth in the BCB Roche system, we reasoned that certain microorganisms, especially when intracelluIar, would grow better in BHI-S broth supplemented with a lysing agent such as saponin (BCB release).…”
mentioning
confidence: 99%
“…In other laboratories the number of days' incubation (number of laboratories) was less than 5 (3), 5-6 (39), 8-10 (32), [14][15][16][17][18][19][20][21] (16). In five laboratories the incubation time depended on the type of bottle and in 14 the incubation period was not stated.…”
Section: Incubation Of Blood Culturesmentioning
confidence: 99%